Transient expression of reporter GFP gene in tissues of Kazakh cotton varieties. (Experimental biology, 2016)
Transient expression of GFP gene in cotton tissues (cotyledons and leaves) were shown. The micrographs showing the transient expression of GFP expression were obtained using the confocal microscope.The green-fluorescent protein (GFP) of the jellyfish Aequoreavictoria has recently been used as a universal reporter in a broad range of heterologous living cells and organisms and GFP is a simple and economical new tool for the direct visualization of promoter activities with a broad range of strength and cell specificity. It can be used to measure dynamic responses of signal transduction pathways, transfection efficiency, and subcellular localization of chimeric proteins, and should be suitable for many other applications in genetically modified living cells and tissues of higher plants.
Keywords: cotton; leaves; cotyledons; GFP-gene; transient expression.